2016
DOI: 10.1371/journal.pone.0167513
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Forest Fragmentation Limits Movements, but Not Occurrence of a Generalist Pollinator Species

Abstract: Habitat loss and fragmentation influence species distributions and therefore ecological processes that depend upon them. Pollination may be particularly susceptible to fragmentation, as it depends on frequent pollinator movement. Unfortunately, most pollinators are too small to track efficiently which has precluded testing the hypothesis that habitat fragmentation reduces or eliminates pollen flow by disrupting pollinator movement. We used radio-telemetry to examine space use of the green hermit hummingbird (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 52 publications
1
45
0
1
Order By: Relevance
“…Some hummingbird species have daily movements of more than 1 km (Hadley & Betts, ) and may exploit resources across different land cover types; for example, a recent study by Volpe et al. () found that the presence of the hummingbird Phaethornis guy in small forest patches is highly dependent in the connectivity of the native forest at the landscape scale. Thus, the use of different land cover types in a landscape may undermine negative effects of land use change at small local scales for many hummingbird species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some hummingbird species have daily movements of more than 1 km (Hadley & Betts, ) and may exploit resources across different land cover types; for example, a recent study by Volpe et al. () found that the presence of the hummingbird Phaethornis guy in small forest patches is highly dependent in the connectivity of the native forest at the landscape scale. Thus, the use of different land cover types in a landscape may undermine negative effects of land use change at small local scales for many hummingbird species.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the strong association found between all three landscape factors and hummingbird functional diversity suggests that relationship between local-scale factors and hummingbirds might be largely dependent on the landscape context (Renjifo, 2001;Tscharntke et al, 2012). Some hummingbird species have daily movements of more than 1 km (Hadley & Betts, 2009) and may exploit resources across different land cover types; for example, a recent study by Volpe et al (2016) found that the presence of the hummingbird Phaethornis guy in small forest patches is highly dependent in the connectivity of the native forest at the landscape scale. Thus, the use of different land cover types in a landscape may undermine negative effects of land use change at small local scales for many hummingbird species.…”
Section: Hummingbird Diversitymentioning
confidence: 99%
“…We separately quantified the landscape composition of these 14 landscapes within two distances surrounding the focal patch representing roughly one (500 m) and two times the radius (1000 m) of species thought to have among the largest home ranges in the system (Volpe et al . ). Composition metrics included the amount of mature tropical forest, regenerating forest (1–3 m tall), agricultural land (primarily coffee/banana plantations), and pasture (Fig.…”
Section: Methodsmentioning
confidence: 97%
“…This change in relative visitation frequencies among pollinator species—only observed for T. intermedia —may be the result of different factors: (i) the populations of certain groups of floral visitors, such as Euglossine bees, are often negatively impacted by habitat loss or fragmentation (e.g. Storck-Tonon and Peres 2017); (ii) the movement of animal pollinators may be constrained by open spaces in fragmented habitats (Volpe et al 2016); and (iii) pollinator behaviour may change along with vegetation structure and floral resources after fragmentation (Goverde et al 2002; Hadley and Betts 2009). In this study, Euglossine bees did not visit Tillandsia flowers in forest fragments, and hummingbirds changed their frequencies according to habitat condition in T. intermedia .…”
Section: Discussionmentioning
confidence: 99%